Conceptualizing the integration of a 3as approach content-based instruction into teaching business english speaking to Chinese EFL undergraduates - Ke Hu; Asmaa AlSaqqaf (Human Resource Management Academic Research Society (HRMARS), 2024)
Economic globalization has changed the demand for cross-cultural communication, making business topics increase exponentially. The need for business English has expanded, and it has evolved into an interdisciplinary major in China’s higher education systems, cultivating bilingual talents in business context. This urges the need for an effective speaking mechanism that facilitates the construction of improved speaking performance. This paper aims to present a conceptual framework that allows for the scaffolding and meaning construction of speaking skills. Regarding this, this study adopts a qualitative approach and uses document analysis as the method of data collection. Unlike previous studies that merely focused on a mono teaching approach, the findings of the study argue that integrating the three stages of skill development approach, which fosters awareness-raising, appropriation, and autonomy of language learners for speaking proficiency, into the content-based instruction can enhance the confidence and interest of Chinese EFL business English undergraduates with diverse backgrounds by engaging them in the proposed activities in the specified phases. Overall, the conceptual framework presented in this paper is hoped to help Chinese EFL business English undergraduates to develop speaking skills.